2021
DOI: 10.1136/bmjresp-2021-000876
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and psychological distress in patients with pulmonary hypertension: a mixed-methods study

Abstract: IntroductionPulmonary hypertension (PH) is a chronic and progressive disease. While prognoses have improved, PH patients still experience side effects and activity restrictions. Accordingly, the key questions asked by this study are ‘How many PH patients have depression/anxiety symptoms?’ and ‘Is there a difference in the symptoms and distress factors between pulmonary arterial hypertension (PAH) and chronic thromboembolic PH (CTEPH) patients, and how are they experiencing distress?’MethodsA mixed-methods stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…In contrast, the anxiety was less prevalent than depression in the present study with prevalence of 17.55%, which was similar to the finding from Japan (10). One study found that patients who had long been diagnosed and followed in a reference center have a lower frequency of psychological disorders than those who had recently been diagnosed with PAH (25).…”
Section: Anxiety and Depression Symptoms Of Patients With Pahsupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast, the anxiety was less prevalent than depression in the present study with prevalence of 17.55%, which was similar to the finding from Japan (10). One study found that patients who had long been diagnosed and followed in a reference center have a lower frequency of psychological disorders than those who had recently been diagnosed with PAH (25).…”
Section: Anxiety and Depression Symptoms Of Patients With Pahsupporting
confidence: 87%
“…These may be because of the poor prognosis, significant side effects, and activity limitations of patients diagnosed of PAH that may expose patients to higher stressors, leading to the development of depression and anxiety (21). High levels of such status can adversely affect health outcomes (22), increase the chance of unhealthy behaviors (23), cause adverse events to occur more frequently (11), and reduce quality of life (10). However, there was a lack of psychological support for PAH patients with depression in the present population, who have not received any type of intervention, and similar observations have been made in the study of Harzheim et al (24).…”
Section: Anxiety and Depression Symptoms Of Patients With Pahmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, two recently published studies corroborate the findings of this review. Takita et al ( 45 ) performed a mixed-methods study, involving both quantitative and qualitative methods, and found PH patients to be more vulnerable to depression and psychological distress. Olsson et al ( 46 ) similarly concluded psychological disorders, including major depression and panic disorder, to be prevalent in PAH patients and these disorders may contribute greatly to the patients' reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%